FOOD SAFETY, EMOTIONAL EXPERIENCE AND HEALTH BEHAVIOUR INFLUENCE ON PURCHASE INTENTION OF NASI LEMAK AMONG MALAYSIANS - Abdullah, Ahmad Shakani bin; Hassan, Ramraini binti Ali; Jeinie, Mohammad Halim bin; Saien, Sairah binti; Nazli, Nik Nadian Nisa binti Nik; Hau, Tan Chi; Hussin, Harniyati (CENTRAL ASIA AND THE CAUCASUS, 2022)
Nasi lemak is one of the traditional foods that has a significant role in the life of Malaysian society. This paper investigated the factors (food safety, emotional experience, health behaviour) that influence the purchase intention of nasi lemak among Malaysians. Survey method was applied in this study. The theoretical framework is based on the Theory of Planned Behavior (TPB). The data were collected from 718 convenience sample using 5-point Likert scale items. Smart PLS was applied to analyse the data. The study revealed the existence of a positive and significant relationship between Emotional experience and health behaviour towards the purchase intention of nasi lemak. It also shows that food safety does not have a significant influence on the purchase intention of nasi lemak. This study adds to the body of knowledge on nasi lemak purchase intent by improving our understanding of consumers' emotional experiences and health behaviours. Only emotional experience and health behaviour were found to have a substantial favourable effect on nasi lemak purchasing intention in Malaysian culture in this study. These findings suggest that by stressing their distinctive benefits and environmentally friendly method, nasi lemak may better match the emotional value and health behaviour of consumers. We also found that food safety has no bearing on nasi lemak buying intent in this study. Other traditional meals should be studied in the future to understand what aspects influence Malaysians' purchasing intentions. Furthermore, this study adds to the knowledge of consumer intent to purchase nasi lemak in developing and rising countries by contributing to the literature on food consumption. In the developing Malaysian scenario, it enables an enlarged TPB model for forecasting nasi lemak purchasing intent.